2004
DOI: 10.1016/j.biolcel.2004.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel Xenopus laevis poly (A) binding protein

Abstract: Poly (A) binding proteins are intimately implicated in controlling a number of events in mRNA metabolism from nuclear polyadenylation to cytoplasmic translation and stability. The known poly(A) binding proteins can be divided into three distinct structural groups (prototypes PABP1, PABPN1/PABP2 and Nab2p) and two functional families, showing that similar functions can be accomplished by differing structural units. This has prompted us to perform a screen for novel poly(A) binding proteins using Xenopus laevis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Very recently, two groups (45,48) independently identified a PABP in Xenopus with 50% amino acid identity to Xenopus PABPN1, called ePABP2. Unlike PABPN1, ePABP2 is localized to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, two groups (45,48) independently identified a PABP in Xenopus with 50% amino acid identity to Xenopus PABPN1, called ePABP2. Unlike PABPN1, ePABP2 is localized to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that ePABP2, like ePAB, may play a role in the cytoplasmic polyadenylation of mRNAs. However, it is noteworthy that Xenopus ePABP2 is present for a much longer period than ePAB (45,48), suggesting that the control of its expression may be independent of ZGA. Moreover, Xenopus ePABP2, unlike Xenopus ePAB, is not able to interact with the cap-binding complex and is therefore unlikely to stimulate translation at the initiation step (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of a sufficient excess of Y-box proteins into in vitro translation systems leads to a translational repression of reporter mRNAs (20 -22). Later studies identified other components of mRNPs, including a DEAD-box ATPase Xp54 and embryonic poly(A)-binding proteins, ePAB and ePABP2 (23)(24)(25)(26)(27). Xp54 and its human homologue RCK repress translation in vitro and/or in oocytes (28,29).…”
mentioning
confidence: 99%